IMMU-21. DIFFERENTIAL EXPRESSION OF ADHESION MOLECULES DEFINES MYELOID CELL INFILTRATION IN GLIOBLASTOMA AND COMPRISES A THERAPEUTIC TARGET. (12th November 2021) - Bayik, Defne; Bartels, Cynthia; Lovrenert, Katreya; Watson, Dionysios; Kay, Kristen; Lauko, Adam; Scacheri, Peter; Lathia, Justin
Abstract: A potently immunosuppressive tumor microenvironment facilitates progression of glioblastoma (GBM). Immunotherapies have had variable success in improving the outcome of GBM patients, suggesting that there is a need to gain insight into the mechanisms of immunosuppression. Myeloid-derived suppressor cells (MDSCs) associate with poor prognosis and treatment resistance of GBM patients, but the distinct role of individual populations is not well-defined. We previous showed that monocytic MDSCs (mMDSCs) accumulated in tumors of mice and patients, while granulocytic MDSCs (gMDSCs) mainly remained in the circulation. Furthermore, nonspecific targeting of mMDSCs with chemotherapies provided therapeutic benefit in preclinical models of GBM, suggesting that mMDSCs drive disease progression. To investigate the differential function of mMDSCs versus gMDSCs in GBM, we adoptively transferred bone marrow-derived MDSC subsets into tumor-bearing mice. Mice that received mMDSCs succumbed to disease sooner compared to control mice, which was not observed with gMDSC transfer. To determine the basis of this pro-tumorigenic activity of mMDSCs, we performed ATAC-sequencing and comparison of differentially accessible regions indicated that cell adhesion pathways were significantly upregulated in mMDSCs. Aligned with this epigenetic profile, mMDSCs from bone marrow and blood had significantly higher surface integrin β1 and integrin β7 expression compared to gMDSCs. To evaluate the role of integrins in MDSC behavior, we pre-treated mMDSCs with anti-integrin β1 prior to adoptive transfer. Blockade of integrin β1 interfered with the pro-tumorigenic role of mMDSCs compared to isotype controls. Similarly, blockade of integrin β1 and integrin β7 systemically extended the survival duration of tumor-bearing mice. Finally, high expression of integrin β1 and integrin β7 served as a poor prognostic indicator in GBM patients. Our findings indicate that modulation of immunosuppressive myeloid cells by leveraging differences in adhesion mechanisms represents a potential immunotherapeutic option for GBM.